Mechanical and Industrial Engineering Historical Aspects and Future Directions - Davim, J. Paulo; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book covers historical aspects and future directions of mechanical and industrial engineering. Chapters of this book include applied mechanics and design, tribology, machining, additive manufacturing and management of industrial technologies. .
Chapter 1. Tribology - A Tool for Mechanical and Industrial Engineering -- Chapter 2. Cutting force modeling: genesis, state of the art, and development -- Chapter 3. Evolution of additive manufacturing processes: from the background to hybrid printers -- Chapter 4. Busbars for e-mobility: State-of-the-art review and a new joining by forming technology -- Chapter 5. Autofrettage: From Development of Guns to Strengthening of Pressure Vessels -- Chapter 6. Machining of Fibrous Composites: Recent Advances and Future Perspectives -- Chapter 7. Management of Industrial Technologies. .
Keywords: Mechanical engineering; Industrial engineering; Production engineering; Machinery; Thermodynamics; Heat engineering; Heat transfer; Mass transfer; Mechanical Engineering; Industrial and Production Engineering; Machinery and Machine Elements; Industrial and Production Engineering; Engineering Thermodynamics, Heat and Mass Transfer